Penerapan Pendekatan Matematika Realistik untuk Meningkatkan Pemahaman Konsep Siswa pada Materi Pokok Dimensi Tiga Kelas XII SMA Negeri 1 Alasa - Alianus Zalukhu; Herman Herman; Magdalena Susanti Telaumbanua; Doni Berkat Tabah Hulu; Nesti Surya Astuti Zebua; Efron Manik; Ruth Mayasari Simanjuntak (Journal on Education, 2023)
Spatial ability in learning mathematics is very important, considering that many students find it difficult to understand objects or geometric shapes. one part of the geometry is three-dimensional matter. Teachers can use approaches, models, or learning strategies that are suitable and theoretically like realistic mathematics education approaches which are expected to improve students' mathematics learning outcomes. The Realistic Mathematics Approach is an approach to learning mathematics that emphasizes the application of mathematics in real-life contexts. Thus learning mathematics will be more effective by using a realistic mathematical approach. A realistic mathematical approach in class XII MIPA 1 SMA NEGERI 1 ALASA can be carried out by analyzing students' mathematical spatial abilities in three-dimensional material seen from initial abilities (high, medium, low) and students' mathematical spatial abilities seen from Bruner's theory (iconic, and symbolic stages ) in three-dimensional matter.